Microhardness and optical property of chalcogenide glasses and glass‐ceramics of the Sn–Sb–Se ternary system. Issue 4 (27th September 2018) - Xue, Xuning; Chen, Feifei; Lin, Changgui; Lin, Ruiqiang; Zhang, Xiaoyu; Dai, Shixun; Zhang, Xianghua; Ji, Wei
Abstract: The microhardness of chalcogenide glasses (ChGs) of the Sn–Sb–Se (SSS) ternary system was investigated, and the correlation of microhardness with the mean coordination number of the SSS ChGs was determined. To prepare infrared‐transparent SSS glass‐ceramics (GCs), two SSS ChGs (A, Sn6.23 Sb14.11 Se79.66 ; B, Sn9.8 Sb17.22 Se72.98 ; by molar composition) were selected and thermally treated at 433 and 448 K, respectively. The improved microhardness (with values that increased by 11.5% and 7.3% for SSS ChG A and B, respectively) of the resulting SSS GCs is attributed to the formation of Sb2 Se3 nanocrystals.